HLA-DR expression in melanoma: from misleading therapeutic target to potential immunotherapy biomarker - Amrane, Karim; Le Meur, Coline; Besse, Benjamin; Hemon, Patrice; Le Noac’h, Pierre; Pradier, Olivier; Berthou, Christian; Abgral, Ronan; Uguen, Arnaud (Frontiers in Immunology, 2024)
Since the advent of anti-PD1 immune checkpoint inhibitor (ICI) immunotherapy, cutaneous melanoma has undergone a true revolution with prolonged survival, as available 5-year updates for progression-free survival and overall survival demonstrate a durable clinical benefit for melanoma patients receiving ICI. However, almost half of patients fail to respond to treatment, or relapse sooner or later after the initial response to therapy. Little is known about the reasons for these failures. The identification of biomarkers seems necessary to better understand this resistance. Among these biomarkers, HLA-DR, a component of MHC II and abnormally expressed in certain tumor types including melanoma for unknown reasons, seems to be an interesting marker. The aim of this review, prepared by an interdisciplinary group of experts, is to take stock of the current literature on the potential interest of HLA-DR expression in melanoma as a predictive biomarker of ICI outcome.